The morphological diversity of plantain in the Democratic Republic of Congo - Adheka, J.G.; Dhed’a, D.B.; Karamura, D.; Blomme, Guy; Swennen, Rony L.; Langhe, E. de (Elsevier, 2018)
This work focused on the morphological characterization of plantain cultivars collected in the period 2005–2014 in 280 villages across 9 provinces of the Democratic Republic of Congo. These cultivars were established in two field collections at the University of Kisangani.Existing descriptors were adapted to better differentiate their variation to address better the taxonomic handicap and the synonymy handicap to improve future research on plantains.Most of the collected cultivars were French plantains (64 out of 98), followed by False Horn (23) and Horn (10) plantains. The bunch type was the main striking difference which allows the quick separation of plantain cultivars into three main types. Other striking differences within plantain were the size of the pseudostem (giant, medium-sized and small-sized) and the bunch orientation (which was generally pendulous or subhorizontal, and rarely horizontal and erect). These three descriptors were considered as main descriptors. Other descriptors (pseudostem colour, immature fruit peel colour, fruit shape, fruit apex, fruit position, number of hands, fruit size, number of fingers per hand and flower relicts at the fruit apex) allowed the differentiation of one cultivar from another within the same main group of bunch type, pseudostem size or bunch orientation. These descriptors are considered as secondary descriptors. Rare descriptors allowed to differentiate one cultivar from all the others in the subgroup. This approach makes the cultivar description logical and faster because it moves from general to particular characteristics, and it offers a platform for reflections on the Pan-African scale of plantain diversity